2014
DOI: 10.1080/13811118.2014.915778
|View full text |Cite
|
Sign up to set email alerts
|

Non-Suicidal Self-Injury among Adolescents in Amman, Jordan

Abstract: While previous research has demonstrated cross-national differences in non-suicidal self-injury (NSSI), most studies to date have taken place in North America. The present study investigated the prevalence and characteristics of NSSI in a sample of 952 Jordanian adolescents (49.8% female) between the ages of 11-19 years. Participants completed a screening measure to assess occurrence of NSSI and its characteristics. Results indicate an overall lifetime prevalence of 22.6% (n = 215), with significantly more mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 49 publications
2
23
0
4
Order By: Relevance
“…Almost a quarter of the adolescents reported that they had intentionally harmed themselves at least once during the past 12 months. This is consistent with results from earlier studies of adolescents in other countries,3 9 but lower than findings from other Chinese cities. 824…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Almost a quarter of the adolescents reported that they had intentionally harmed themselves at least once during the past 12 months. This is consistent with results from earlier studies of adolescents in other countries,3 9 but lower than findings from other Chinese cities. 824…”
Section: Discussionsupporting
confidence: 92%
“…Beyond prevalence rates and methods, research on the body location of NSSI remains limited. A small number of studies have shown that the common injury locations involve the arms, legs and the head, with gender differences reported for type and location of injury among adolescents 3 10. For example, Hanania and colleagues3 investigated the characteristics of NSSI in a sample of 952 Jordanian adolescents (49.8% female) between the ages of 11 and 19 years and found that females were more likely than males to engage in cutting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of NSSI behaviors have been reported as between 16 and 44 percent (Kokaliari, 2014; Prinstein et al, 2010; Whitlock et al, 2011). The majority of these studies have been conducted in the United States, but evidence from other countries suggest similar rates in, for example, Italy, Jordan, and Indonesia (Gholamrezaei et al, 2015; Hanani et al, 2014; Tresno et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Taiwan, two studies among high school students reported rates of 22.4 percent (Chen, 2006) and 11.3 percent (Tsai et al, 2011). Finally, in Jordan, a study of self-injury among 950 adolescents reported a lifetime prevalence of 22 percent and that males were more likely than females to self-injure (Hanania et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%